Question
upstudy study bank question image url

Given two functions \( f(x)=4 \cdot 2^{x} \) and \( g(x)=4 \cdot 5^{x} \), find and simplify the following: a) \( (f g)(x)=\square \) b) \( \left(\frac{f}{g}\right)(x)=\square \)

Ask by Christensen Peters. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a) \( (f \cdot g)(x) = 16 \cdot 10^{x} \) b) \( \left(\frac{f}{g}\right)(x) = \left(\frac{2}{5}\right)^{x} \)

Solution

a) To find (f · g)(x), multiply the two functions:   f(x) = 4 · 2^x  and g(x) = 4 · 5^x. Thus,   (f · g)(x) = (4 · 2^x) · (4 · 5^x) = 16 · 2^x · 5^x. Since 2^x · 5^x = (2·5)^x = 10^x, we have:   (f · g)(x) = 16 · 10^x. b) To find (f/g)(x), divide the two functions:   (f/g)(x) = (4 · 2^x) / (4 · 5^x). The 4's cancel, leaving:   (f/g)(x) = 2^x / 5^x = (2/5)^x. Thus, the simplified forms are:  a) 16 · 10^x  b) (2/5)^x.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the products and quotients of the functions \( f(x) \) and \( g(x) \), let's start with each calculation. a) The product of \( f(x) \) and \( g(x) \) is: \[ (f g)(x) = f(x) \cdot g(x) = (4 \cdot 2^{x}) \cdot (4 \cdot 5^{x}) = 16 \cdot 2^{x} \cdot 5^{x} \] We can combine \( 2^x \cdot 5^x \) into a single exponential term: \[ = 16 \cdot (2 \cdot 5)^{x} = 16 \cdot 10^{x} \] So, \[ (f g)(x) = 16 \cdot 10^{x} \] b) The quotient of \( f(x) \) by \( g(x) \) is: \[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{4 \cdot 2^{x}}{4 \cdot 5^{x}} = \frac{2^{x}}{5^{x}} \] This can be simplified as: \[ = \left(\frac{2}{5}\right)^{x} \] Thus, the final results are: \[ (f g)(x) = 16 \cdot 10^{x} \] \[ \left(\frac{f}{g}\right)(x) = \left(\frac{2}{5}\right)^{x} \]

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy